Identification of HIV-1 Reverse Transcriptase-Associated Ribonuclease H Inhibitors Based on 2-Hydroxy-1,4-naphthoquinone Mannich Bases - Nhat Quang Tu; Clémence Richetta; Federica Putzu; Olivier Delelis; Khursheed Ahmed; Vijay H. Masand; Rainer Schobert; Enzo Tramontano; Angela Corona; Bernhard Biersack (Molecules)
There is a strong demand for new and efficient antiviral compounds. A series of 2-hydroxy-1,4-naphthoquinone Mannich bases were screened for their HIV-1-RNase H inhibitory activity. An HIV-1-RNase H assay was used to study the RNase H inhibition by the test compounds. Docking of active derivatives into the active site of the enzyme was carried out. Compounds 1e and 2k showed distinctly higher HIV-1-RNase H inhibitory activity (IC50 = 2.8–3.1 µM) than the known inhibitors RDS1759 and compound 13. The binding mode and possible interactions of 1e and 2k with the HIV-1-RNase H active site were determined using molecular docking, which led to the identification of salient and concealed pharmacophoric features of these molecules. The docking analysis revealed that there are significant differences in the binding mode of these compounds within the active site of the target enzyme. A selection of HIV-1-RNase H-inhibitory Mannich bases was tested for antiviral activity against HIV-1, and compound 2k showed the highest activity at low toxicity to host cells. The lawsone Mannich bases 1e and 2k also underwent a preliminary screening for activity against SARS-CoV-2, and compound 1e was found to inhibit SARS-CoV-2 replication (IC50 = 11.2 µM).